(untitled) (Revista Brasileira Multidisciplinar, 2020)
The present research is a study in the format of review, on Grounded Theory (GT) methodology in the area of computing. Starting from the question: in the production of knowledge in the field of computing, is the GT methodology used? If this methodology is used, how does it operate? The general objective is to verify if GT is used or not and, if it is used, how it contributes or has contributed to the advancement of knowledge in the area of computing. The methodology used in this text is of a qualitative approach and applies bibliographic research, in which, in addition to the survey, some notes are organized about the presence of the GT in the area of computing and provides reflections based on authors of this area regarding the use of the GT. The results indicate that the GT is present in 3% of the productions in the area and does not generate consubstantial theories, nor theory, only the methodology is used for the purposes of a brief analysis of data / phenomena, among the various objects of study in this area. One of the directions of this review is to encourage the formation of new researchers who will make the GT operational in their investigations in the field of computing, both in terms of technological, industrial, commercial, etc. as well as in investigations aimed at undergraduate courses in the area.